The Impact of Psychological Trauma on Finance: Narrative Financial Therapy Considerations in Exploring Complex Trauma and Impaired Financial Decision Making - D. Bruce Ross III; Ed Coambs (Journal of Financial Therapy, 2018)
The current paper aims to foster new discussion on the complex, deleterious, and conflated relationship between psychological trauma and financial management processes. Trauma and financial distress are interconnected, affecting the cognitive, behavioral, emotional, and relational aspects of our lives. A case vignette is presented for financial therapists which utilizes an integrated, trauma-informed approach addressing the lasting impact of childhood trauma on financial management behaviors and the client’s life story. Treatment modalities consider narrative financial therapy, four categories of sexual and financial shame, and four phases of trauma restoration. Ethical and practice implications are discussed.
Keywords: Emotional Trauma; Finances; Financial Behavior; Financial Management; Financial Therapy; Psychological Trauma; Sexual Abuse